Prospective randomized and crossover comparison of two apheresis machines for peripheral blood stem cell collection: a multicenter study. Issue 11 (29th August 2016) - Ikeda, Kazuhiko; Minakawa, Keiji; Muroi, Kazuo; Fujiwara, Shin‐ichiro; Yamada‐Fujiwara, Minami; Fujimori, Yoshihiro; Tanosaki, Ryuji; Ohto, Hitoshi; ,
Abstract : BACKGROUND: Improving apheresis technology may lead to an efficient and safe peripheral blood stem cell (PBSC) collection. Recently, the Spectra Optia (Optia, Terumo BCT) was introduced as an automated apheresis instrument, but comparisons with other instruments have been few. This is the first randomized multicenter and crossover comparison of the Optia with the automated program of the established apheresis instrument, the Spectra (Spectra‐Auto, Terumo BCT). STUDY DESIGN AND METHODS: A total of 233 apheresis procedures performed in 46 autologous patients and 108 allogeneic donors were investigated. Apheresis performed in the first day for all subjects using the Spectra‐Auto (n = 79) and the Optia (n = 75) were evaluated as first‐day analysis. Seventy‐nine subjects, who required another session on the second day, underwent apheresis using the other instrument than the first‐day instrument and were compared with each other in a paired crossover analysis. RESULTS: The two instruments processed similar volumes with comparable run times and volumes of acid‐citrate‐dextrose used. The volumes of collected products were greater in the Optia. Yields of mononuclear cells and CD34+ cells were not different, but collection efficiencies were higher in the Optia (p = 0.008 in CE1 of crossover analysis). Spectra‐Auto–collected products contained more contaminating red blood cells (RBCs), whereas there was a trend of more contaminating platelets (PLTs) in the Optia‐collected products. Slight reductions were noted in the RBC or PLT counts of subjects who underwent apheresis with the Spectra‐Auto or the Optia, respectively. CONCLUSION: The Optia is safe and more efficient in the PBSC collection compared with the Spectra‐Auto.